Identification and Characterization of the Nitrobenzene Catabolic Plasmids pNB1 and pNB2 in Pseudomonas putida HS12 - Park, Hee-Sung (American Society for Microbiology, 2000)
Pseudomonas putida HS12, which is able to grow on nitrobenzene, was found to carry two plasmids, pNB1 and pNB2. The activity assay experiments of wild-type HS12(pNB1 and pNB2), a spontaneous mutant HS121(pNB2), and a cured derivative HS124(pNB1) demonstrated that the catabolic genes coding for the nitrobenzene-degrading enzymes, designated nbz, are located on two plasmids, pNB1 and pNB2. The genes nbzA, nbzC, nbzD, and nbzE, encoding nitrobenzene nitroreductase, 2-aminophenol 1,6-dioxygenase, 2-aminomuconic 6-semialdehyde dehydrogenase, and 2-aminomuconate deaminase, respectively, are located on pNB1 (59.1 kb). Meanwhile, the nbzB gene encoding hydroxylaminobenzene mutase, a second-step enzyme in the nitrobenzene catabolic pathway, was found in pNB2 (43.8 kb). Physical mapping, cloning, and functional analysis of the two plasmids and their subclones in Escherichia coli strains revealed in more detail the genetic organization of the catabolic plasmids pNB1 and pNB2. The genes nbzA and nbzB are located on the 1.1-kb SmaI-SnaBI fragment of pNB1 and the 1.0-kb SspI-SphI fragment of pNB2, respectively, and their expressions were not tightly regulated. On the other hand, the genes nbzC, nbzD, and nbzE, involved in the ring cleavage pathway of 2-aminophenol, are localized on the 6.6-kb SnaBI-SmaI fragment of pNB1 and clustered in the order nbzC-nbzD-nbzE as an operon. The nbzCDE genes, which are transcribed in the opposite direction of the nbzA gene, are coordinately regulated by both nitrobenzene and a positive transcriptional regulator that seems to be encoded on pNB2.